Effectiveness study of Malaysia monetary policy on economic growth / Nur Hidayah Ahmad Zaini - Ahmad Zaini, Nur Hidayah (Faculty of Business and Management, 2018)
This paper aims to investigate the effectiveness study of Malaysia monetary policy on economic growth. In this study, Malaysia is selected because of the developmental strides that the Malaysia economy has experienced in the past several decades and as the case of Malaysia can be adopted as a role model for many developing countries in the attempts to improve the economies. Malaysian is an upper middle income developing the country with a population of 3 1.62 million. The study will concentrate on the interactions between monetary policy instrument particularly interest rate, money supply, unemployment rate, foreign direct investment and GDP per capita which will serve as the instrument for measuring economic growth. The purpose of the studies is to find the relationship between dependent variable and independent variable, whether they have any correlation between each other or not. The studies used quantitative secondary data which is time series data and multiple regression model as the technique to look at the fluctuation of GDP per capita. There will be 40 observation over the period of 2008 QI until 2017 Q4 that derived from Thomson Reuters Datastream. The expected finding showed the interest rate, money supply, unemployment rate, and foreign direct investment have a significant influence on economic growth. Therefore, this study can be advantageous in various ways. It will provide an objective perspective of the effectiveness of monetary policy in Malaysia, which is a developing country and this in-depth understanding of the Malaysian economy can help other similar countries in the formulation of their own policies.